Dendritic cell and macrophage infiltration in microsatellite-unstable and microsatellite-stable colorectal cancer - Bauer, Kathrin; Michel, Sara; Reuschenbach, Miriam; Nelius, Nina; Knebel Doeberitz, Magnus von; Kloor, Matthias (Familial cancer, 2011)
High level microsatellite instability (MSI-H) is a hallmark of Lynch syndrome-associated colorectal cancer (CRC). MSI-H CRC express immunogenic tumour antigens as a consequence of DNA mismatch repair deficiency-induced frameshift mutations. Consequently, frameshift antigen-specific immune responses are commonly observed in patients with Lynch syndrome-associated MSI-H CRC. Dendritic cells (DC) and macrophages play a crucial role in the induction and modulation of immune responses. We here analysed DC and macrophage infiltration in MSI-H and microsatellite-stable CRC. Sixty-nine CRC (MSI-H, n = 33; microsatellite-stable, n = 36) were examined for the density of tumour-infiltrating DC, Foxp3-positive regulatory T cells, and CD163-positive macrophages. In MSI-H lesions, S100-positive and CD163-positive cell counts were significantly higher compared to microsatellite-stable lesions (S100: epithelium P = 0.018, stroma P = 0.042; CD163: epithelium P < 0.001, stroma P = 0.046). Additionally, numbers of CD208-positive mature DC were significantly elevated in the epithelial compartment of MSI-H CRC (P = 0.027). High numbers of tumour-infiltrating Foxp3-positive T cells were detected in tumours showing a low proportion of CD208-positive, mature DC among the total number of S100-positive cells. Our study demonstrates that infiltration with DC, mature DC, and macrophages is elevated in MSI-H compared to microsatellite-stable CRC. The positive correlation of Foxp3-positive Treg cell density with a low proportion of mature DC suggests that impaired DC maturation may contribute to local immune evasion in CRC. Our results demonstrate that DC and macrophages in the tumour environment likely play an important role in the induction of antigen-specific immune responses in Lynch syndrome. Moreover, impaired DC maturation might contribute to local immune evasion in CRC.